PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PRODUK ORIFLAME DI KOTA BATAM - Setyorini, Eka Kartika; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2019)
At present, competition in the field of beauty is quite strict, along with technological and cultural developments, so that it can influence the increase in community needs, usage patterns and how to meet the needs in the field of beauty. The purpose of this study is to find out some of the effects of prices on customer satisfaction and the effect of service quality on customer satisfaction and at the same time determine the influence of price and service quality on customer satisfaction. This type of research is quantitative descriptive. The analysis technique in this study is multiple linear regression analysis. The research data is processed with SPSS version 21 software program. This test uses validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination, t-test and f-test. In this study, the population consisted of customers who used oriflame products with a total sample of 100 respondents. The conclusion is that the price variable is partially, but not significant, influences customer satisfaction and that service quality variables have a significant effect on customer satisfaction, while at the same time the variable price and service quality have a significant influence on customer satisfaction.